Connected audiences in digital media markets: The dynamics of university online video impact - Germán López-Buenache; Ángel Meseguer-Martínez; Alejandro Ros-Gálvez; Alfonso Rosa-García (European Research on Management and Business Economics (ERMBE), 2022)
This paper analyses whether the audience dynamics of one content provider can explain the audience dynamics of a different content provider, and the resulting network of connections among providers. The type of connections in this network determines whether the audience of one creator influences or is susceptible to other creators' audience. Granger causality networks are applied to prestigious universities that provide online videos on YouTube and the structure of the Audience Dynamics Network is described. This network presents an unbalanced degree distribution and a core-periphery structure. The centrality of the universities in the network is discussed and universities with influential and susceptible roles are identified. We find that audience connection is determined by the differences in the online video impact between each pair of universities. Centrality in the network is associated with university prestige, but this relation is mediated by online video impact.
Keywords: A20; I20; L14; 650; Digital media markets; Granger causality networks; Online video; Time series; World-class universities